THE EFFECT OF MOTIVATION ON EMPLOYEE PERFORMANCE AT THE OGO MALANE DRINKING WATER REGIONAL COMPANY, TOLITOLI REGENCY: PENGARUH MOTIVASI TERHADAP KINERJA KARYAWAN DI PERUSAHAAN AIR MINUM REGIONAL OGO MALANE, KABUPATEN TOLITOLI - Sahwan Sahwan; Rizki Wahyudi Mahmud (STIE MUJAHIDIN TOLITOLI, 2025)
Tolitoli Regency. This study uses a quantitative approach with a simple linear regression analysis method. The total sample was 54 respondents who were active employees of Ogo Malane. The independent variable studied is motivation, while the dependent variable is employee performance. The results of the study show that motivation has a positive and significant effect on employee performance. This is evidenced by a significance value of 0.000 < 0.05 and a tcal value of 3.794 > a ttable of 2.006. The determination coefficient (R²) of 0.217 indicates that motivation contributes 21.7% to the improvement of employee performance, while the remaining 78.3% is influenced by other variables that were not studied. The average motivation score of respondents was in the